Multi-item replineshment model of inventory management in Small Medium Enterprises in Malaysia - Irfan Ur, Rahman (2022)
In the international context, small and medium businesses are rapidly expanding, but they have received little attention, especially in Malaysia. Many previous studies have concentrated on the degree of issues and challenges that SMEs face, and to a lesser extent, on the maximum potential that SMEs in this country possess. The most common issue that manufacturing SMEs in Malaysia face is poor inventory management and a lack of proper lean manufacturing tool, both of which have an impact on the organization's efficiency. Manufacturing SMEs have been found to be unable to compete effectively in the manufacturing sectors due to a lack of inventory management skills. According to the SME annual report 2017/2018, there is a substantial annual increase of 20% in the operation cost of the manufacturing SMEs recorded in a quarterly survey conducted from the third quarter of 2015 to third quarter of 2017. For this purpose, the objectives of the research are to find the barriers of Kanban system in local SMEs in Malaysia for Kanban framework, to propose a multi-item inventory model in Malaysia’s SMEs and to validate the applications of the developed inventory model at selected SMEs. The study investigated barriers in the implementation of Kanban system in Malaysia’s SMEs and provided a framework that will enable SMEs to implement Kanban system successfully. The research methodology is designed to distribute questionnaire survey to the local SMEs to collect data for the development of Kanban framework. As per objective of the study framework was developed accordingly by SPSS analysis. The research has also developed Economic order quantities in objective 2, for a multi-item inventory model with financial and storage constraints for SMEs. The findings of this research have shown that the model has reduced the order quantities for Akhtar Munir Manufacturing Sdn. Bhd. by 22.27%, Al Taj food marketing and services by 32.93% and Dusaf Musa Maju by 15.97% in order to satisfy the given condition of financial and storage resources.